(3GdeYdheGJ h UfGYI GdfTQ (B/s - (3GdYSGajf, YjSi YjSis ((3OeTb (B:s (3OGQ GdacQ ddWHGYI h GdfTQ h GdJhRjY ,s, 2001)
(3jbSe GdcJGH Gdi CQHYI CbSGe QFjSjI JYGdL eaghe GdeYdheGJ h aFGJgG h SeGJgG h KhQJgG h JMdd eaghe GdfTQ aj EWGQ GdPGcQI GdNGQLjI h GdeQMdI GdhQbjI aj eSjQI UfGYI GdfTQ h cPdcGdGJLGgGJ GdYOOjI h GdfhYjI ddEfJGL GdacQj GdShQj h ef Ke GdeQMdI GddGhQbjI dUfGYI GdfTQ h bVGjG GdfTQ GdEdcJQhfj Hjf GdeSGfOjf ddcJGH GdhQbj h GdeHTQjf HCbhdgs
Keywords: (3GdHjHdjhLQGajIs; (3GdfTQ GdEdcJQhfjs; (3Yde GdecJHGJ h GdeYdheGJs; (3GdYSGajfs